Unilateral Biportal Endoscopic Tumor Removal and Percutaneous Stabilization for Extradural Tumors: Technical Case Report and Literature Review - Kim, Seung-kook; Bendardaf, Riyad; Ali, Murtaza; Kim, Hyun-a; Heo, Eun-jung; Lee, Su-chan (Frontiers in Surgery, 2022)
Background: Extradural spinal tumors arise from soft or bony tissue in the spine and account for the majority of spinal tumors. Interest in the unilateral biportal endoscopic (UBE) technique is rising because it can easily decompress the bony spinal canal and accommodate all open surgical instruments under endoscopic guidance. However, reports of this technique have been limited to certain diseases. This study first demonstrates a UBE technique for extradural tumor biopsy, removal, and percutaneous stabilization in a 72-year-old female patient with dramatic symptom improvement. Methods: We used the UBE technique for decompression and the percutaneous screw fixation technique for stabilization in a patient with an extradural mass compressing the thecal sac and destroying the posterior element. Under endoscopic guidance, a unilateral approach was used, and decompression and flavectomy were performed bilaterally. After decompression, tumor removal and biopsy were performed using various forceps and biopsy needles. After confirming sufficient spinal canal decompression, the screw was placed percutaneously. We evaluated the technical process of the procedure, the patient’s pre- and postoperative pain (using the visual analog scale), and operative radiology and pathologic results. Results: Postoperative pain and disability improved clinically, and spinal alignment stabilized radiologically. As the pathology findings confirmed an aneurysmal bone cyst, the treatment was completed without adjuvant therapy. Conclusions: We treated an unstable spine due to an extradural tumor with the UBE and percutaneous screw techniques.